2021
DOI: 10.3389/fphar.2021.790072
|View full text |Cite
|
Sign up to set email alerts
|

Qingwenzhike Prescription Alleviates Acute Lung Injury Induced by LPS via Inhibiting TLR4/NF-kB Pathway and NLRP3 Inflammasome Activation

Abstract: Background: Acute lung injury (ALI) is characterized by dysfunction of the alveolar epithelial membrane caused by acute inflammation and tissue injury. Qingwenzhike (QWZK) prescription has been demonstrated to be effective against respiratory viral infections in clinical practices, including coronavirus disease 2019 (COVID-19) infection. So far, the chemical compositions, protective effects on ALI, and possible anti-inflammatory mechanisms remain unknown.Methods: In this study, the compositions of QWZK were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 50 publications
(51 reference statements)
1
28
0
Order By: Relevance
“…Therefore, the dosage of XZR-middle is almost equivalent to the human clinical dose, and the low dose is half of the equivalent clinical dose, while the high dose is double the equivalent clinical dose. The doses of XZR extract used in rats in this study were also consistent with that in most previous studies, that is, the dosage of decoction in rodents reached crude drug g/kg/day ( Jiang et al, 2020 ; Zhang et al, 2021 ). It is worth emphasizing that the quantitative analysis of bioactive compounds in XZR and studies on the low dose levels assessing the therapeutic effect of XZR decoction warrant further exploration in the future.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the dosage of XZR-middle is almost equivalent to the human clinical dose, and the low dose is half of the equivalent clinical dose, while the high dose is double the equivalent clinical dose. The doses of XZR extract used in rats in this study were also consistent with that in most previous studies, that is, the dosage of decoction in rodents reached crude drug g/kg/day ( Jiang et al, 2020 ; Zhang et al, 2021 ). It is worth emphasizing that the quantitative analysis of bioactive compounds in XZR and studies on the low dose levels assessing the therapeutic effect of XZR decoction warrant further exploration in the future.…”
Section: Discussionsupporting
confidence: 90%
“…The rat dose in our study was calculated based on the body surface area and the corresponding clinically prescribed dose for a 70 kg human body [70.01 g (raw herbs)/70 kg/day] ( Zhang et al, 2021 ). Therefore, the dosage of XZR-middle is almost equivalent to the human clinical dose, and the low dose is half of the equivalent clinical dose, while the high dose is double the equivalent clinical dose.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators extracted the abstracts and titles and identified 38 studies that met the inclusion criteria. After reviewing all of the publications, 10 studies were excluded because of missing outcome data ( Ehrhart et al, 2000 ; Tawadros et al, 2007 ; Nader and Baraka, 2012 ; An et al, 2014 ; Wang et al, 2015 ; Liu and Chen, 2016 ; Shen et al, 2017 ; Ni et al, 2019 ; Wang et al, 2019 ; Yang et al, 2019 ), and another 12 studies were excluded because multiple interventions were investigated ( Murakami et al, 2000 ; Lin et al, 2011 ; Li et al, 2014b ; Li et al, 2016a ; Li et al, 2016b ; Baradaran Rahimi et al, 2019 ; Ye et al, 2019 ; Duan et al, 2020 ; Yue et al, 2020 ; Choi et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022 ). In conclusion, 16 studies were included in this meta-analysis, as described below ( Shi et al, 2007 ; Yang et al, 2011 ; Chen et al, 2014 ; Yang et al, 2014 ; Yuan et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Li et al, 2018b ; Luo et al, 2019 ; Ren et al, 2019 ; Zhang et al, 2020 ; Ali et al, 2021 ; Dikmen et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…TP53, CASP3, and BCL2 play an important role in the regulation of apoptosis signal transduction, and the ALI mechanism has been proved to be closely related to apoptosis[28]. Inhibiting the activation of TLR-4/NF-κB signal pathways can reduce the secretion and expression of inflammatory cytokines, such as TNF-α and IL-1β and reduce the inflammatory cascade reaction and thus reduce inflammation’s damage to the lung[29, 30]. The GO and KEGG pathways analysis shows that the NF-kappa B signalling pathway, TNF signalling pathway, MAPK signalling pathway, apoptosis, p53 signalling pathway, HIF-1 signalling pathway and Coronavirus disease - COVID-19 were the key targets signal pathways.…”
Section: Discussionmentioning
confidence: 99%
“…TP53, CASP3, and BCL2 play an important role in the regulation of apoptosis signal transduction, and the ALI mechanism has been proved to be closely related to apoptosis [28]. Inhibiting the activation of TLR-4/NF-κB signal pathways can reduce the secretion and expression of inflammatory cytokines, such as TNF-α and IL-1β and reduce the inflammatory cascade reaction and thus reduce inflammation's damage to the lung [29,30]…”
Section: Discussionmentioning
confidence: 99%